A construção do sentimento de infância: análise a partir da iconografia e historiografia - Ramos, Ana Paula Lira (Universidade Federal do Tocantins, 2025)
This article analyzed the construction of the feeling of childhood as a historical category as hegemonic thought through iconography and historiography, in which we observed the medieval child as a mini-adult, the bourgeois child and children's clothing, and finally, the adultized child of the 21st century. This theme is considered essential in times when children are the target of consumerist stimuli, adult incentives and school obligations that lead them to grow up before their time through responsibilities and commitments that are reminiscent of an adult's routine. In this way, the research aimed to discuss the constitution of the feeling of childhood identified in canvas paintings from the 12th century onwards and the relevance of the role played by children in capitalist society through 19th century photographs. This is a bibliographical study, supported by authors who study childhood, such as Ariès (1986), Postman (1999), Oliveira (2008) and Buckingham (2003). The research showed that childhood is a historical construction that has undergone changes according to society, culture and social class. In contemporary times, children are encouraged to grow up more quickly through adult behaviors and obligations reinforced by school, family and the media.